An appraisal of Australian Brahman Development project in Ang Thong province, Thailand - Song, Young-duk; Boonjit Titapiwatanakun; Sornthep Tumwasorn; Upasena, Selawa H.; Asian Institute of Technology Partial (Bangkok : Asian Institute of Technology, 1994)
The cattle (Australia Brahman) production system in the Ang Thong province, Thailand was monitored for one month in March, 1994. Data were obtained by interviewing small scale farmers (120 cases) in Ang Thong province about characteristics of farmers, farm management, cost, income, and major problems in production system. The main objectives of this study were to analyses the performance of the imported cattle (Australia Brahman) for the beef production in the area. It is purposed this study will leads to a better management raising. Four different schemes of breeding were hypothesized in accordance with data surveyed for the analysis of a profitability of the cattle farming. The results of the study indicated that most of farms were small scale farmers and using traditional technology and indigenous knowledge to raise cattle. Shortage of labor and feed were found to be significant constraints faced by farmers. Because there was not much natural grass during the dry season and no family labor during the farming season especially rice cultivation. In addition, the market price of cattle has recently been declining, this has became the biggest problem for the farmers. This low market price is due to the large influx of cattle from neighboring countries. NPV (Net Present Value), B/C Ratio (Benefit/Cost Ratio) and IRR (Internal Rate of Return) are the main measurement applied to evaluate the cattle system. There are two types of estimated indicators, one is concerned with incomes and costs in cash only and the other is concerned with incomes and costs in cash and non-cash. NPV in cash only is found at 18,565.4 baht and that of cash and non-cash is 986.78 baht. In the same way, IRR in cash is 14.4 and in cash and non-cash is 6.47. In cash B/C ratio is 1.698 and 1.012 is both cash and non-cash respectively. There is no significant benefit based on B/C ratio and NPV, when concerning total cost and income (cash + noncash). However, once cash cost and income are considered the profitability increase substantially. This is mainly due to high family labor cost and the low market price of cattle. If farmer makes a habit of recording a performance of cattle, an income, expenditure, etc on the weekly basis it is nature that he predict not only what he has to do now but also what he will prepare for cattle in a future. A food shortage is one of the most problems, pasture is the solution of it. Farmer affirmatively agreed training is essential to practice cattle farm and may be able to influence on many aspects in terms of cattle farming.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources & Development
Thesis (M.Sc.) - Asian Institute of Technology, 1994
Keywords: Cattle -- Thailand -- Ang Thong -- Development